Adapting reading tasks in the textbook Basic English for computing" to teach reading skills to students at Centre of Information Technology Development = Điều chỉnh các nhiệm vụ đọc trong giáo trình "Basic English for computing" tại trung tâm phát triển C - Bùi, Thanh Nga (ĐHNN, 2017)
46 p. + CD-ROM